SUCCESSFUL USE OF BRENTUXIMAB VEDOTIN IN THE TREATMENT OF PROGRESSIVE PERIPHERAL UNSPECIFIED T-CELL LYMPHOMA IN AN ELDERLY FEMALE PATIENT - L. G. Gorenkova; S. K. Kravchenko; E. E. Klebanova; K. I. Danishyan; M. A. Silaev; A. M. Kovrigina; N. V. Rizikova; N. I. Skidan; M. A. Ceitlina; V. G. Savchenko (Онкогематология, 2017)
Peripheral T-cell lymphoma not otherwise specified (PTCL-NOS) is a rare subgroup of lymphomas. This disease is predominantly found in older people and often has extranodal involvement including skin and soft tissues. To verify the diagnosis, it is necessary to perform histological and immunohistochemical tests, which show the expression of CD30 activation antigen in different proportions (less than 10 %, not more than 80 %) in addition to the expression of other T-cell antigens (CD2, CD4, CD5, CD7). When choosing the induction regimen in older people with relevant cardiac history, it is preferable to use non-anthracycline-containing chemotherapy courses. However, despite the low intensity of such regimens, treatment of elderly patients is associated with high risk of side effects. Using new drugs (monoclonal antibodies, epigenetic agents) in combination with polychemotherapy is a promising direction opening a possibility of successful management for all patients including those older than 65 years. In the described clinical case of PTCL-NOS, the patient had primary refractory disease. Significant clinical response (complete remission) was achieved as a result of targeted therapy with brentuximab vedotin containing anti-CD30 chimeric antibody conjugated to a microtubuledisrupting agent (monomethyl auristatin E) without toxicity and any infections. In case of ambiguous situation (an increase in the size of one of the tumor sites with regression of others, signs of infection – hyperemia, perifocal edema, the spread of the necrosis zone), histological verification is necessary to confirm the disease progression.